Problematika Jilbab Cadar dan Burqa pada Masyarakat Indonesia: Analisis Metode Tafsir Maudhu’i - Fadly Alanka; Ilham Musthofa AQ; Fadia Luthfi Riyani; Hanifatul Auliya; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2023)
This article discusses the problems of headscarves, veils, and burqas in Indonesian society. This study uses a descriptive methodology and maudhu'i interpretation. This qualitative research methodology relies on secondary data sources, namely works of literature related to the research topic taken from books, articles, journals, and other sources. In the real world and in cyberspace, the hijab and veil fashion trend has experienced very volatile developments, especially among teenagers. Thus, people tend to misunderstand the true meaning of the hijab. Because the hijab is used as a fashion trend, so it does not rule out the possibility of wearing the hijab or headscarf not in accordance with Islamic law. Islam only requires its people to wear clothes that cover their genitals and not to wear clothes that are out of habit where they live. As long as it does not contain any unlawful elements, Islam punishes it as permissible or permissible.